স্মৃতির কল্লোলে : সন্দ্বীপের গোলাম নবী পণ্ডিতের বংশগাঁথা - চৌধুরী, সেলিনা
Family history of landlords from Sandwīp Island, Bangladesh; includes articles on the life of Golāma Nabī Paṇḍita, landlord from Sandwīp and some anecdotes of author.